2016
DOI: 10.1016/j.ijrobp.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gene Alterations and Tyrosine Kinase Inhibition on Survival and Cause of Death in Patients With Adenocarcinoma of the Lung and Brain Metastases

Abstract: Purpose Lung cancer remains the most common cause of both cancer mortality and brain metastases (BM). The purpose of this study was to assess the effect of gene alterations and tyrosine kinase inhibition (TKI) on median survival (MS) and cause of death (CoD) in patients with BM from lung adenocarcinoma (L-adeno). Methods A multi-institutional retrospective database of patients with L-adeno and newly diagnosed BM between 2006 and 2014 was created. Demographics, gene alterations, treatment, MS, and CoD were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
60
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 24 publications
8
60
1
Order By: Relevance
“…Mutations in epidermal growth factor receptor are more prevalent among the Japanese population and are associated with delayed onset of brain metastases and longer survival after treatment. (11, 12) Further study of adjuvant WBRT may warrant attention to gene alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in epidermal growth factor receptor are more prevalent among the Japanese population and are associated with delayed onset of brain metastases and longer survival after treatment. (11, 12) Further study of adjuvant WBRT may warrant attention to gene alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the impact of biomarkers on prognostication for patients with BM from primary breast and NSCLC has led to modifications of the GPA. 34 , 35 This information is not available within the current cohort, which may also be a limitation; however, in practice, these data may either be unavailable or rendered irrelevant once patients have progressed through all available lines of systemic therapy. Additionally, we were unable to abstract quality of life, steroid dependence, setting of care, and KPS after completion of repeat WBRT.…”
Section: Discussionmentioning
confidence: 99%
“…However, independent prognostic factors vary depending on the primary tumor site, and other biological makers may also play roles. The recently published NSCLC-specific Lung-molGPA index is the first to incorporate both traditional factors, such as patient age and gender, and EGFR and ALK mutation status [ 16 , 17 ]. Our assessment showed that the Lung-molGPA index offers medium OS predictive ability in lung adenocarcinoma patients with BMs.…”
Section: Discussionmentioning
confidence: 99%
“…To further refine the NSCLC-specific GPA, a new prognostic system, Lung-molGPA, was proposed based on 2,186 NSCLC patients with BMs. This new system included not only age, KPS, extracranial metastases, and number of BMs, but also EGFR and ALK mutation status [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%